So, We Have Two Problems To Solve:
(-3)÷((-1/3) ÷ (8-4)) ÷ (-12/5)
And
(-1/3)*2÷(7/3 * (-1))÷(-6/5)
So, Lets Do The First One:
We Know That We Need To Use Order Of Operations.
We Need To First Do:
8-4.
8 - 4 = 4.
So, We Have Now:
(-3)÷((-1/3) ÷ 4) ÷ (-12/5)
So, We Need To Now Convert 4 To An Improper Fraction.
This Becomes 4/1.
Now, We Can Divide (-1/3) By 4.
Dividing Is The Same As Multiplying By The Reciprocal.
So:
-1 1 -1
--- * --- = ---
3 4 12
So, We Now Have:
(-3)÷ (-1/12) ÷ (-12/5)
So:
3 12 36
--- * --- = --- = -36
1 -1 -1
So, We Now Have:
-36 ÷ (-12/5)
So:
-36 -5 -180
----- * ---- = ------
1 12 12
So, We Now Only Have Left to Divide:
-180 ÷ 12 = -15.
So, The Value Of The First Question Is -15.
Now For Number Two:
(-1/3)*2÷(7/3 * (-1))÷(-6/5)
So, We Use Order Of Operations.
7/3 * (-1) = -7/3
Next:
(-1/3)*2÷(-7/3)÷(-6/5)
Now, We Must Do:
-1/3 * 2.
(-1/3) * 2 = (-2/3)
So, Now We Have:
(-2/3) ÷ (-7/3) ÷ (-6/5)
Now, Begin Division.
-2 3 -6 6
--- * --- = ---- = ----
3 -7 -21 21
So:
6/21 ÷(-6/5)
Do The Final Division:
6 5 30
--- * --- = ----
21 -6 -126
Simplify:
30 ÷ 6 5
------ = -----
-126 ÷ 6 -21
So, Number Two Has A Value Of 5/-21.